2013
DOI: 10.3350/cmh.2013.19.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of gastric variceal bleeding: retrospective Korean multicenter data

Abstract: Background/AimsWhile gastric variceal bleeding (GVB) is not as prevalent as esophageal variceal bleeding, it is reportedly more serious, with high failure rates of the initial hemostasis (>30%), and has a worse prognosis than esophageal variceal bleeding. However, there is limited information regarding hemostasis and the prognosis for GVB. The aim of this study was to determine retrospectively the clinical outcomes of GVB in a multicenter study in Korea.MethodsThe data of 1,308 episodes of GVB (males:females=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…1 To date, the bleeding of gastric varices remains to be a tough problem, which was full of challenges. [2][3][4] Transjugular intrahepatic portosystemic shunt (TIPS), acted as a mini-invasive interventional surgery, has a good effect on the therapy of gastric and esophageal varices, and consequently has been widely used in the last several decades, especially for the patients who did not have a good state and other treatments was not suitable for.…”
Section: Introductionmentioning
confidence: 99%
“…1 To date, the bleeding of gastric varices remains to be a tough problem, which was full of challenges. [2][3][4] Transjugular intrahepatic portosystemic shunt (TIPS), acted as a mini-invasive interventional surgery, has a good effect on the therapy of gastric and esophageal varices, and consequently has been widely used in the last several decades, especially for the patients who did not have a good state and other treatments was not suitable for.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies show that GVO is more effective and safer than endoscopic gastric variceal sclerotherapy and ligation in the management of acute GVB 26-29. Also, Mahadeva et al have reported that GVO was more cost effective than TIPS in the management of acute GVB 30.…”
Section: Discussionmentioning
confidence: 99%
“…Also, among the many related factors, the Child-Pugh score and MELD score were significantly associated with mortality. Kim et al have reported that the Child-Pugh score and MELD score contributed to predicting survival of the patients with GVB 29,32. This suggests that important factors in predicting the prognosis of GVB are the severity of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…BRtO and modified-BRtO (mBRtO using coil or vascular plug instead of balloon) are receiving increased attention for the management of bleeding gastric varices [6][7][8] . BRTO has a high efficacy in stopping acute gastric variceal bleeding and has shown to have a signifi cantly lower re-bleeding rate of gastric varices compared to tIPS or endoscopic treatment [9][10][11][12][13][14] . Recently, our group has shown the effectiveness of mBRtO using coils or vascular plugs in place of balloons [15][16][17] , which is comparable to conventional BRtO [8][9][10][11][12]18,19] .…”
Section: Introductionmentioning
confidence: 99%